Association of ACEI/ARB therapy with total and cardiovascular death in coronary artery disease patients with advanced chronic kidney disease: a large multi-center longitudinal study - Wenguang Lai; Xiaoli Zhao; Tingting Zhang; Donghui Huang; Guoxiao Liang; Yang Zhou; Jin Liu; Shiqun Chen; Yong Liu (Renal Failure)
Introduction Advanced chronic kidney disease (CKD) is common among patients with coronary artery disease (CAD), and angiotensin‑converting enzyme inhibitors (ACEI) or angiotensin‑receptor blockers (ARB) can improve cardiac and renal function, but whether ACEI/ARB therapy improves long-term prognosis remains unclear among these high-risk patients. Therefore, this research aimed to investigate the relationship between ACEI/ARB therapy and long-term prognosis among CAD patients with advanced CKD.Methods CAD patients with advanced CKD were included in five hospitals. Advanced CKD was defined as estimated glomerular filtration rate (eGFR)<30 ml/min per 1.73 m2. Cox regression models and competing risk Fine and Gray models were used to examine the relationship between ACEI/ARB therapy and all-cause and cardiovascular death, respectively.Results Of 2527 patients, 47.6% population of our cohort was discharged on ACEI/ARB. The overall all-cause and cardiovascular mortality were 38.6% and 24.7%, respectively. Multivariate Cox regression analyses indicated that ACEI/ARB therapy was found to be associated with lower rates of both all-cause mortality (hazard ratio (HR)=0.836, 95% confidence interval (CI): 0.738–0.948, p = 0.005) and cardiovascular mortality (HR = 0.817, 95%CI: 0.699–0.956, p = 0.011). In the propensity-matched cohort, the survival benefit was consistent, and significantly better survival was observed for all-cause mortality (HR = 0.856, 95%CI: 0.752–0.974, p = 0.019) and cardiovascular mortality (HR = 0.830, 95%CI: 0.707–0.974, p = 0.023) among patients treated with ACEI/ARB.Conclusion ACEI/ARB therapy showed a better survival benefit among high-risk CAD patients with advanced CKD at long-term follow-up, which manifested that strategies to maintain ACEI/ARB treatment may improve clinical outcomes among these high-risk populations.